CR-submanifolds of a nearly trans-Sasakian manifold - Falleh R. Al-Solamy (International Journal of Mathematics and Mathematical Sciences)
This paper considers the study of CR-submanifolds of a nearly trans-Sasakian manifold, generalizing the results of trans-Sasakian manifolds and thus those of Sasakian manifolds.